Effect of Two Antibacterial Luting Protocols with and without Immediate-Dentin-Bonding on Microtensile Bond Strength of Glass Ceramic to Bur-Cut Cavity Floor Dentin - Izgi Ayça Deniz; Kaya Eylem; Kale Ediz; Zortuk Mustafa (Balkan Stomatological Society, 2021)
Background/Aim: The aim of this study was to evaluate the bond strength of glass ceramic inlay system using 2 antibacterial adhesive luting protocols with 2 cementation techniques to bur-cut dentin.